Risk factors and prognosis analysis of gastrointestinal bleeding combined with hemorrhagic shock in patients in intensive care unit:A retrospective study - Changfu Liu; Jinju Li (PLoS ONE, 2026)
Background Through retrospective analysis of clinical data on gastrointestinal bleeding complicated with hemorrhagic shock (GIB-HS) in patients in our intensive care unit（ICU）, we aim to explore relevant risk factors and prognosis, and provide guidance for clinical prevention and treatment of such cases. Methods A total of 93 cases of gastrointestinal bleeding from October 2023 to January 2025 in the Intensive Care Medicine Department of our hospital were collected. Based on the presence or absence of hemorrhagic shock, they were divided into a hemorrhagic shock group (observation group, n = 42 cases) and a control group (control group, n = 51 cases). The differences in clinical data between the two groups were analyzed, and logistic regression was used to analyze the risk factors for gastrointestinal bleeding complicated with hemorrhagic shock. The sensitivity and specificity of predicting hemorrhagic shock were analyzed using the receiver operating characteristic（ROC）curve, and the prognosis of the two groups was compared. Results There were statistically significant differences in the scores of type 2 diabetes, urea nitrogen, red blood cell number, hemoglobin, hematocrit and Acute Physiology and Chronic Health Evaluation II(APACHEII) score, P ＜ 0.05. Binary logistic regression analysis was conducted with factors with P < 0.1 as independent variables. The results showed that there was a statistically significant difference in urea nitrogen and fibrinogen, which were risk factors for ICU GIB-HS The ROC curve showed that urea nitrogen had the highest specificity in predicting ICU patients with GIB-HS, while fibrinogen had the highest sensitivity in predicting hemorrhagic shock. Compared with the prognosis of the two groups, the mortality rate of the group with hemorrhagic shock was higher than that of the group without hemorrhagic shock. Conclusions An exploratory correlation analysis revealed that both urea nitrogen and fibrinogen are factors associated with the prediction of GIB-HS in ICU patients, while APACHEII score, respiratory failure, and fibrinogen are independent factors affecting the prognosis of ICU patients with GIB-HS. Clinicians need to timely identify these indicators and optimize treatment plans to improve prognosis. 1. Patients with advanced malignant tumors, 2. Age of onset<18 years, 3. Pregnant or lactating women, 4. Incomplete case or follow-up data.